Effects of zooplankton abundance on the spawning phenology of winter-spawning Downs herring (Clupea harengus) - Marchal, Paul; Giraldo, Carolina; Johns, David; Lefebvre, Sébastien; Loots, Christophe; Toomey, Lola (PloS one, 2025)
We have investigated phenological shifts in autumn- and winter-spawning Atlantic herring ( Clupea harengus ) in the Eastern English Channel and the Southern North Sea (Downs component), in relation to temperature and the availability of potential zooplanktonic prey ( Calanus finmarchicus , Calanus helgolandicus , Temora longicornis ). A two-tiered approach building on the monthly distribution of commercial herring landings was developed, which consisted of, (1) calculating the timing and duration of spawning season based on estimated deviations from basic harmonic signals and, (2) analysing their inter-annual variations in relation to biotic (zooplankton abundance) and abiotic (temperature) environmental variables through time series analyses. The start, midpoint and ending of herring spawning season were increasingly delayed over the period 1999–2021, a process which was correlated with the abundance of Calanus finmarchicus . The resulting duration of spawning season slightly decreased. Direct effects of sea temperatures on any phenological metrics could not be clearly evidenced. Different ecological processes were likely involved in the start and ending of spawning season. Additional covariates (including size/age composition, the biotic and abiotic factors other than those examined in our study) could contribute to a better explanation of the phenological drift in Downs herring spawning.